The Influence of Promotion Through Pokdarwis Social Media on the Decision to Visit Menange Rambang Tourism - Subandi; Yousf Bellin Swarli (Cigarskruie: Journal of Educational and Islamic Research, 2024)
The aim of this research is to see the influence of promotion through social media (X) on the decision to visit Menange Rambang Tourism, Surabaya Village, East Sakra District, East Lombok Regency. The sample used in this research was 30 respondents. The data analysis method used was simple linear regression including prerequisite assumption tests. Based on the results of the regression test, it was found that promotion through social media (X) had a significant effect on the decision to visit Menange Rambang Tourism, Surabaya Village, East Sakra District, East Lombok Regency (Y). This is proven by a sig value of 0.000 < 0.05 in a positive direction. The promotion variable through social media (X) influences the decision to visit Menange Rambang Tourism, Surabaya Village, East Sakra District, East Lombok Regency (Y) by 37.3%, while 62, 7% is influenced by variables outside of observation.